Troubling nationhood in U.S. Latina literature : explorations of place and belonging - Socolovsky, Maya, 1973- (Latinidad., 2013)
This book examines the ways that U.S. Latina literature challenges popular definitions of nationhood and national identity. It explores the works of Mexican American, Puerto Rican, and Cuban American writers Denise Chavez, Ana Castillo, Sandra Cisneros, Judith Ortiz Cofer, Esmeralda Santiago, and Himilce Novas to show how these texts argue for the legitimate belonging of Latino/as within U.S. borders and counter anti-immigration rhetoric.